Foreign aid, urbanization and green cities - Jun Li (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Rapid urbanization, and particularly the associated problems of urban poverty, unsustainable development and environmental degradation, pose an enormous challenge to many developing countries. In the last decade more foreign aid has been diverted to urbanization and green city development. This paper studies aid's implementation strategies and effectiveness by investigating 'what works in foreign aid on urbanization and green cities', 'what could work', and 'what is scalable and transferable in foreign aid on urbanization and green cities'. Three case studies are carried out: Tianjin City which was constructed according to a newly designed eco-city plan, Wenchuan and Beichuan which needed to be re-built after an earthquake, and Curitiba which rose from an existing city. The paper shows that a transferable and scalable aid framework which combines concerns related to poverty, environment and governance both at policy and implementation level is needed in order for aid to succeed in supporting developing countries' urbanization and green city development.
Keywords: O1; Q1; R1; Z1; 330; developing countries; sustainability; aid effectiveness; scalable; transferable; framework; Urbanisierung; Nachhaltige Stadtentwicklung; Nachhaltige Entwicklung; Entwicklungshilfe; Entwicklungsländer